Annual Reports : conception and design of annual reports = konzeption und gestaltung von jahresberichten = conception et desing de rapports annuels - Lewis, Richard A. (Graphis, 1971)
This book on the conception and design of annual reports is the first comprehensive work on the subject so far published. It sets out to describe the genesis of the medium, to review its headlong development in the last few decades and to give all those involved in its presentation hints and advice on how to go about the job. In the pictorial section, our illustrations are less documentation of the text than examples of outstand-ing annual report design. Since the annual report was, up to a few years ago, chiefly an American phenomenon, much of what is said relates specifically to the United States. The author of the text, Richard A. Lewis, ranks among the very foremost authorities in the field and is President of Corporate Annual Reports, Inc., a creative team that has planned, written, designed and produced over 250 reports in the past nine years. While emphasis on America reflects the status quo, it does not make this book any the less international. This point is underlined by the reproduction of numbers of good examples of report design from other coun-tries. For the fact is that the rise of the annual report to prominence in America is now rapidly being followed by a parallel development in Europe and elsewhere. The annual report thus presents a growing challenge to corporations, designers and communicators all over the world. This book is meant as a stimulant and a standby to them in their endeavors.